Electron transfer via the non-Mtr respiratory pathway from Shewanella putrefaciens CN-32 for methyl orange bioreduction. (August 2020) - Min, Di; Cheng, Lei; Liu, Dong-Feng; Li, Wen-Wei; Yu, Han-Qing
Graphical abstract: Highlights: Methyl orange reduction by S. putrefaciens CN-32 occurred via cleavage of azo bond. Methyl orange reduction by S. putrefaciens CN-32 not via metal respiratory pathway. A distinctive electron transfer path was involved in methyl orange reduction. Regulators and periplasmic c -type cytochromes involved in methyl orange reduction. Abstract: Exoelectrogens play the core roles in bioelectrochemical systems (BESs) because of their unique extracellular electron transfer capacity to different electron acceptors. Microbial reduction of azo dyes by exoelectrogens under anaerobic conditions has received great attention because of its eco-friendliness, low cost, and unique extracellular reduction ability. In this work, we unexpectedly found that Shewanella putrefaciens CN-32 adopted a distinctive electron transfer mechanism for bioreduction of MO (methyl orange) compared to the other exoelectrogens. MO reduction by S. putrefaciens CN-32 occurred through mechanisms that were not dependent on the known azoreductase and the Mtr (metal-reducing) respiratory pathway. Some anaerobic regulators (e.g., Fur and EtrA) and periplasmic c -type cytochromes (Sputcn32_2333) might involve in MO reduction by S. putrefaciens CN-32. The major reduction products were 4-aminobenzenesulfonic acid (4-ABA) and N, N-dimethyl-p-phenylenediamine (DPD) and the initial cell density in the reduction system affected MO reduction kinetics by S. putrefaciens CN-32. Moreover, S. putrefaciens CN-32 could utilize multiple mediators such as flavins or anthraquinone-2, 6-sodium disulfonate (AQDS) to accelerate MO reduction. Our findings provide a new perspective on the reduction mechanisms of azo dyes by exoelectrogens and might facilitate more efficient utilization of them in BESs for treatments of azo dyes-polluted industrial effluents.